Tatak Pilipino [episode no. 72][videorecording]. ([Quezon City ABS-CBN], 1992)
Summary: A unique display of Pilipino ways and style.
Contents: Historical rap calendar events of May (5 min.) -- Melanie Marquez (10 min.) -- Santacruzan ng mga bakla (5 min.) -- Bayani (15 min.) -- Caravan, the traveling supermarket (15 min.) -- Mga artista sa politika (5 min.)
Credits: Hosts, Jim Paredes and Gel Santos Relos.
Keywords: Marquez, Melanie; Actors -- Philippines; Gays -- Philippines; Heroes -- Philippines; Wagons -- Philippines; Philippines -- History; Sociology